2002
DOI: 10.3171/spi.2002.97.4.0440
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a resorbable anterior cervical graft containment plate

Abstract: ✓ In this article the authors review the history of anterior cervical plating for one- and two-level discectomy for degenerative disease and provide background justification for the design and testing of a cervical plate composed of a resorbable material. The design of the plate is discussed with special reference to modifications of its design and tools compared with metallic plates that are necessary because of the different mechanical properties of the less rigid material. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Also, thanks to the transparency of the plates, it is possible to observe the intervertebral graft during the fixation of the plate, a point that other colleagues have remarked as well [12,26].…”
Section: Discussionmentioning
confidence: 94%
“…Also, thanks to the transparency of the plates, it is possible to observe the intervertebral graft during the fixation of the plate, a point that other colleagues have remarked as well [12,26].…”
Section: Discussionmentioning
confidence: 94%
“…30 It has also been suggested that the presence of a titanium plate is undesirable to patients-even shortterm use of a collar may be preferable to the long-term presence of a metal plate. 31 Graft containment and proper load sharing to minimize graft subsidence may be a more critical role for cervical plates. Bioresorbable plates exhibit a more physiologic stiffness and are resorbable, and may therefore reduce adjacent level degeneration while providing adequate graft-containment.…”
Section: Discussionmentioning
confidence: 99%
“…The device is presently not intended for load-bearing applications. 7 Current implants are manufactured from a medical grade polylactic acid copolymer [70/30 poly (L-lactideco-D,L-lactide)], which is degraded and resorbed through the process of bulk hydrolysis and is ultimately metabolized into carbon dioxide and water. The gradual resorption of the PLDLA polymer allows for gradual physiological transfer of forces to the graft, theoretically decreasing stress shielding and increasing the rate of graft incorporation.…”
Section: Discussionmentioning
confidence: 99%